Innovative catalysis in organic synthesis : oxidation, hydrogenation, and C-X bond forming reactions - Andersson, Pher G., 1963- (Wiley-VCH ; John Wiley [distributor], 2012)
"Authored by a European team of leaders in the field, this book compiles innovative approaches for C-X bond forming processes frequently applied in organic synthesis. It covers all key types of catalysis, including homogeneous, heterogeneous, and organocatalysis, as well as mechanistic and computational studies. Special attention is focused on the improvement of efficiency and sustainability of important catalytic processes, such as selective oxidations, hydrogenation and cross-coupling reactions. The result is a valuable resource for advanced researchers in both academia and industry."--Provided by publisher.